The Efficiency of the Application of Electronic Techniques in the Control of Dynamic Balance in the Process of Inclusive Physical Education - Oksana Blavt; Rostyslav Chaplinskyі; Mykola Prozar; Maryan Pityn; Tetiana Helzhynska; Vitalii Dmytruk; Oleh Hrebik; Volodymyr Kovalchuk (OVS LLC, 2023)
The purpose of the study was to determine the authenticity of the dynamic balance control device developed on the basis of modern trends in the field of electronic equipment for students with disabilities. Materials and methods. 32 students with disabilities, aged 18-24 years, I-III years of study, who received a doctor's permission to participate in testing and had vestibular disorders, were selected for the studied sample, in accordance with the provisions of voluntariness and anonymity. General scientific methods of gathering theoretical information, the method of technical modeling, pedagogical testing and methods of mathematical statistics were used. Results. A dynamic balance control device was developed on the basis of the most up-to-date electronic equipment and programming. The device consists of an integrated electronic unit, a programmable microcontroller system unit, and a PC. The information received by the capacitive sensors placed in the unit of the integrated electronic unit during the student's performance of the test task is processed in the unit of the programmable microcontroller system and transmitted via non-contact infrared communication lines to the PC where it is graphically presented. To establish the authenticity of testing using the developed device, reliability and validity coefficients were determined, which in numerical values reached a "high" level, in contrast to the test the results of which were recorded directly by the teacher and numerically corresponded to the limits of "low" and "medium". Conclusions. The dynamic balance control device presented in the work is designed using the most up-to-date electronic equipment and programming. Considering the importance of eliminating vestibular disorders and related dynamic balance disorders in students with disabilities, the use of the presented development of the control device in the practice of inclusive PE is aimed at ensuring the effectiveness of this process. The integration of a control device developed based on current trends in the field of electronic equipment into the inclusive physical education of students with disabilities is the basis for the development of new approaches in the process of dynamic balance testing based on objective assessment.